The influence of diverse optical wavelengths on growth rate of Chlorella Vulgaris microalgae - Trofimchuk, O A; Yakovlev, A N; Turanov, S B; Trigub, M V; Romanenko, S A (IOP conference series. Materials Science and Engineering, 2020)
The effect of different optical wavelengths on growth and development of microalgae had been examined repeatedly. Many articles had been published over the subject, although the results of these investigations were frequently controversial. Depending on the number of days spent on cultivation process, yield gain could be both significant and barely noticeable. Also, irradiation intensity plays vital part in microalgae functioning.